3(x-y)-2(y-x)=

Simple and best practice solution for 3(x-y)-2(y-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-y)-2(y-x)= equation:


Simplifying
3(x + -1y) + -2(y + -1x) = 0
(x * 3 + -1y * 3) + -2(y + -1x) = 0
(3x + -3y) + -2(y + -1x) = 0

Reorder the terms:
3x + -3y + -2(-1x + y) = 0
3x + -3y + (-1x * -2 + y * -2) = 0
3x + -3y + (2x + -2y) = 0

Reorder the terms:
3x + 2x + -3y + -2y = 0

Combine like terms: 3x + 2x = 5x
5x + -3y + -2y = 0

Combine like terms: -3y + -2y = -5y
5x + -5y = 0

Solving
5x + -5y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5y' to each side of the equation.
5x + -5y + 5y = 0 + 5y

Combine like terms: -5y + 5y = 0
5x + 0 = 0 + 5y
5x = 0 + 5y
Remove the zero:
5x = 5y

Divide each side by '5'.
x = y

Simplifying
x = y

See similar equations:

| (7x-2)=(-4x+13) | | 7x=4(x-8)+3x | | 0.2x+0.5(13-x)=3.8 | | -u^2+8u-16=0 | | 5(a-b)-2(a-b)+8(a-b)= | | (9x+5)=(11x-25) | | 10000*3.12= | | 88=(5+2y)*y | | 3(2b-a)-(2a-b)= | | (X^2+2x+40)=(x^2)-x+190 | | m(x)=x^5-10x^4+25x^3 | | 8(x+y)+3(x+y)= | | 4a+7a=9 | | 4.5x-1.8=3.2x+0.8 | | X^2=3+x | | z+2.6z-5.5=(z-0.3) | | 6(x-y)-3(3x+y)= | | -4.2-6y-4.7-2y=-7y-1.3 | | 4x-12=-48 | | 4(y-7x)-y= | | 5z=18z | | 5z=8z | | 10-(2z-1)=1-3z | | (4x-3)(x-5)=(-11x+1)(3x-2) | | 4x^2-56x+184=0 | | 12x-3y+x+2y= | | 7+f=1+4f | | 4x^2-40x+100=44 | | 7f=1+4f | | 2x^2+4x=3 | | 4*x-3=2x*-3-2 | | 3*2x-5=2x-7 |

Equations solver categories